Treatment Options for Hepatitis Delta Virus Infection - Heidrich, Benjamin; Manns, Michael P.; Wedemeyer, Heiner (Current infectious disease reports, 2013)
The hepatitis D virus (HDV), the smallest virus known to infect man, causes the most severe form of chronic viral hepatitis, hepatitis delta. It is estimated that about 15 to 20 million people are suffering from chronic HDV infection. HDV is a defective satellite virus depending on the hepatitis B surface antigen (HBsAg) for transmission. Chronic hepatitis delta is associated with a rapid progression of liver fibrosis and a high prevalence of liver cirrhosis, even in younger patients. Immunization against hepatitis B virus (HBV) protects from HDV infection, but there is no specific vaccine against HDV available for HBsAg-positive individuals. Treatment options for hepatitis delta patients are limited. So far, only interferon-alpha has shown an antiviral efficacy against HDV. Recent trials showed sustained virological response rates concerning HDV in 25 %–30 % of patients treated with pegylated interferons. HDV is dominant over HBV in the majority of cases, but HBV DNA-positive subjects should be treated with HBV polymerase inhibitors. Combination therapy of pegylated interferon-alpha and adefovir showed a more pronounced HBsAg decline, but the exact role of combination therapies in hepatitis delta requires further investigation. Alternative future treatment strategies may include prenylation inhibitors and HBV entry inhibitors, which are in early clinical development.